1994
DOI: 10.1515/cclm.1994.32.11.813
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Determination of Gut Permeability in Man with M r 400, M r 1500, M r 4000 and M r 10 000 Polyethylene Glycol

Abstract: Parlcsak and Bode: Gut pcrmeabiiity of K 400, M r 1500, M r 4000 and M r 10000 polyethylene glycol in man 813 Eur. J. Clin. Chcm. Clin. Biochem. Vol. 32, 1994, pp. 813-820 © 1994 Summary: Polyethylene glycol has been in use for a number of years for the assessment of gut permeability. The methods so far employed are usually limited to polyethylene glycols in the low relative molecular mass r nge (up to M T 1300). We developed a method for the simultaneous determination of gut permeability to M r 400, M r 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
2
30
0
1
Order By: Relevance
“…Parenteral injections of radiolabeled polyvinylpyrrolidone in humans demonstrated that the permeability cut-off of the human small intestine is MW of 80 000 Da. 24,25 The GI permeability "cut-off" MW was also confirmed using polyethylene glycol (PEG) 26,27 and, even for patients with irritable bowel syndrome, it is below 80 000 Da 28,29 and therefore an order of magnitude below the MW of PTFE which is in the million Das.…”
Section: Review Of Biological Safety Of Ptfementioning
confidence: 94%
“…Parenteral injections of radiolabeled polyvinylpyrrolidone in humans demonstrated that the permeability cut-off of the human small intestine is MW of 80 000 Da. 24,25 The GI permeability "cut-off" MW was also confirmed using polyethylene glycol (PEG) 26,27 and, even for patients with irritable bowel syndrome, it is below 80 000 Da 28,29 and therefore an order of magnitude below the MW of PTFE which is in the million Das.…”
Section: Review Of Biological Safety Of Ptfementioning
confidence: 94%
“…Finally PEGs were resolubilized in 1-mL of high-performance liquid chromatography solvent consisting of methanol:H 2 O (66:34 volume). Aliquots of 200 µL were analyzed in quadruplicate by high-performance liquid chromatography (pump M510, automatic injector WISP 710B, differential refractometer R401; Waters, Eschborn, Germany and 2 serial connected columns LiChroCart 250 · 10; Merck, Darmstadt, Germany) under isocratic conditions with a solvent flow of 1 mL/min according to Parlesak et al 32 Biliary phospholipids and bile acids were measured by a commercial kit (Boehringer Mannheim, Mannheim, Germany) and a 3␣-steroid dehydrogenase assay, 33 respectively. Standard analysis procedures served for the estimation of lipids, liver enzymes, bilirubin, and differential blood counts in plasma and whole blood.…”
Section: Methodsmentioning
confidence: 99%
“…After transmigration into the blood, the polar PEGmolecule is excreted with the urine. Because of its homogeneous chemical properties, its appropriately adaptable molecular mass and its linear, chain-like shape (mimicking the comparable structure of endotoxin) [28] , PEG seems to be an appropriate probe for the assessment of LPS translocation through the intestine. All of these demands cannot be met by other commonly used permeability marker compounds such as mono-or disaccharides, sugar alcohols, complexes with radioactive nuclides (51Cr-EDTA, 99mTc-DTPA), proteins, or even combinations of these compounds [29] .…”
Section: Cirrhotics Without Ascites (N = 27)mentioning
confidence: 99%